Prognosis of transphyseal hematogenous osteomyelitis in children: three case reports and a literature review - Peng Ning; Shuting Lin; Zhixin Yang; Tianjing Liu (BMC Musculoskeletal Disorders)
Abstract Background Transphyseal hematogenous osteomyelitis(THO) has been considered a potential cause of severe sequelae due to its damage to the growth plate. It has been reported that growth disturbance would take place if the area of involvement exceeds 7%. However, the growth plate seems to have more potential to recover and regain normal function. Case presentation We report three cases of hematogenous osteomyelitis(HO) in children (ages 9 weeks, 4 years, and 13 years respectively ) with significant physeal involvement. All patients underwent surgical debridement and antibiotic therapy. Follow-up assessments demonstrated full recovery, with normal knee movements, no pain and equal limb length. Complete recovery of the physeal plate morphology and normal subsequent development were observed. Conclusions THO in children may have the chance of complete recovery after proper treatment, suggesting that the physeal plate has a great potential for self-recovery. Clinical trial number Not applicable.